2016
DOI: 10.1021/acs.jmedchem.5b01549
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Structure–Activity Relationship of a Bioactive Fragment of ELABELA that Modulates Vascular and Cardiac Functions

Abstract: ELABELA (ELA) was recently discovered as a novel endogenous ligand of the apelin receptor (APJ), a G protein-coupled receptor. ELA signaling was demonstrated to be crucial for normal heart and vasculature development during embryogenesis. We delineate here ELA's structure-activity relationships and report the identification of analogue 3 (ELA(19-32)), a fragment of ELA that binds to APJ, activates the Gαi1 and β-arrestin-2 signaling pathways, and induces receptor internalization similarly to its parent endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
185
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(211 citation statements)
references
References 51 publications
21
185
0
Order By: Relevance
“…Finally, intravenous injection of K17F in increasing doses in lactating rats increases diuresis in a dose-dependent manner concomitantly with a significant decrease in urine osmolality and a decrease in AQP2 insertion at the apical membrane of CD (77), showing that K17F-induced diuresis is linked to a direct action of apelin on CD. Similarly, in other studies (78, 79), acute or chronic intravenous treatment with apelin-13 potently increased diuresis in male Sprague-Dawley rats.…”
Section: Physiological Effects Of Apelinsupporting
confidence: 70%
“…Finally, intravenous injection of K17F in increasing doses in lactating rats increases diuresis in a dose-dependent manner concomitantly with a significant decrease in urine osmolality and a decrease in AQP2 insertion at the apical membrane of CD (77), showing that K17F-induced diuresis is linked to a direct action of apelin on CD. Similarly, in other studies (78, 79), acute or chronic intravenous treatment with apelin-13 potently increased diuresis in male Sprague-Dawley rats.…”
Section: Physiological Effects Of Apelinsupporting
confidence: 70%
“…In physiological conditions, both ligands exert powerful cardiac and vasoactive actions . Indeed, infusion of apelin‐13 increases cardiac contractility while decreasing cardiac loading (positive inotropic effect), dilates blood vessels without compromising their permeability, and promotes blood vessel sprouting . Similar results were observed with ELA .…”
Section: Introduction—the Apelinergic Systemsupporting
confidence: 58%
“…Indeed, infusion of apelin‐13 increases cardiac contractility while decreasing cardiac loading (positive inotropic effect), dilates blood vessels without compromising their permeability, and promotes blood vessel sprouting . Similar results were observed with ELA . While the apelinergic system is abundantly expressed in endothelial cells to regulate the properties of the vascular system, recent findings highlighting its significant expression in platelets suggest it might exert antithrombotic actions that require further study .…”
Section: Introduction—the Apelinergic Systemsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies investigating the metabolism of apelin peptides were largely conducted in plasma in vitro or in rodent models neither of which may represent metabolism in humans. These studies demonstrated that apelin peptides are very labile in plasma with a half-life of less than 1-5 minutes in vitro [20][21][22][23][24] . This plasma instability has to date been attributed the enzymatic activity of neprilysin 25 and angiotensin converting enzyme II (ACE2) [22][23][24] , and more recently plasma kallikrein 26,27 .…”
mentioning
confidence: 94%